PUBLIC-PRIVATE PARTNERSHIP AT IMPLEMENTATION OF URBAN DEVELOPMENT PROJECTS - T. Daskalova (Trakia Journal of Sciences)
Public-private partnership is a significant alternative for the local development. The projects based on this cooperation are main instruments for solution of social-economic and structural problems of the cities. The purpose of the publication is identification of the prerequisites, the problems and the possibilities for improvement of the elaboration and the implementation of projects for urban development in Bulgaria. Desk analysis, empirical analysis and other scientific methods are applied for the attainment of the purpose in the research. Main deficits are synthesized as a result of the analysis at an institutional and operational level of the public-private partnership. Perspectives for improvement of the potential for successful implementation of projects for sustainable development of the cities are outlined as conclusion.